Pendampingan Guru dalam Pengembangan E-Learning Berbasis OBE untuk Pembelajaran Seni Musik di Kelas IV SDN 10 Kabupaten Buton Tengah - Ridwan Ardi (Prodi PGSD Unsultra, 2026)
21st-century learning requires teachers to integrate digital technology and learning approaches oriented toward student competency achievement. One relevant approach is Outcome-Based Education (OBE), which focuses the learning process on measurable and meaningful learning outcomes. In the context of Music Arts learning in elementary schools, integrating OBE with e-learning is crucial because music learning requires audio-visual media and practice-based activities. However, observations at SDN 10, Central Buton Regency, indicate that teachers still face challenges in designing OBE-based Music Arts learning and optimally utilizing e-learning. This community service activity aims to improve teachers' capacity in designing, implementing, and evaluating OBE-based Music Arts learning through an e-learning platform. The method used is a participatory mentoring approach, which includes needs analysis, training and workshops, digital material development, implementation support, and monitoring and evaluation. The results of the activity indicate a significant increase in teacher competency in formulating OBE-based learning outcomes, developing teaching modules, developing e-learning media, and implementing performance-based assessments. Teachers successfully developed digital content in the form of videos, audio, and interactive worksheets that were uploaded to the school's e-learning platform. The implementation of this learning in the classroom demonstrated increased student activity, creativity, and engagement in the music project. Thus, teacher mentoring in the development of OBE-based e-learning has proven effective in improving the quality of Music Arts learning in fourth-grade students at SDN 10, Central Buton Regency. The integration of OBE and e-learning provides a more meaningful, creative, and relevant learning experience to meet the demands of 21st-century education